The Brain of the Archerfish Toxotes chatareus: A Nissl-Based Neuroanatomical Atlas and Catecholaminergic/Cholinergic Systems - Karoubi, Naomi; Segev, Ronen; Wullimann, Mario F. (Frontiers in Neuroanatomy, 2016)
Over recent years, the seven-spot archerfish (Toxotes chatareus) has emerged as a new model for studies in visual and behavioral neuroscience thanks to its unique hunting strategy. Its natural ability to spit at insects outside of water can be used in the lab for well controlled behavioral experiments where the fish is trained to aim at targets on a screen. The need for a documentation of the neuroanatomy of this animal became critical as more research groups use it as a model. Here we present an atlas of adult T. chatareus specimens caught in the wild in South East Asia. The atlas shows representative sections of the brain and specific structures revealed by a classic Nissl staining as well as corresponding schematic drawings. Additional immunostainings for catecholaminergic and cholinergic systems were conducted to corroborate the identification of certain nuclei and the data of a whole brain scanner is available online. We describe the general features of the archerfish brain as well as its specificities, especially for the visual system and compare the neuroanatomy of the archerfish with other teleosts. This atlas of the archerfish brain shows all levels of the neuraxis and intends to provide a solid basis for further neuroscientific research on T. chatareus, in particular electrophysiological studies.